Localization and regulation by GABA of anion transporter present in pollen grain protoplasts and tube of Arabidopsis thaliana - Domingos, Patrícia (2016)
Tese de doutoramento, Biologia (Biologia do Desenvolvimento), Universidade de Lisboa, Faculdade de Ciências, 2015